An Improved Method for Optimizing the Benefits of Capacitor Application in Radial Feeders - Abellana, Arsenio A. (Philippine Engineering Journal, 2021)
The sizing, location and combination of capacitor banks to be placed in a radial distribution feeder for loss reduction and voltage control – is thoroughly investigated in this research work. The quantification of the benefits of voltage profile improvement and a thorough analysis for fixed and switched capacitor combinations are the main features of this work. Solution algorithms together with the corresponding computer programs and derivations of the equations are presented here. A mathematical model of a single-ended radial feeder, with real and reactive loadings assumed known at once hour intervals, was simulated in the IBM 360 UP Engineering Computer. The results show that the consideration of monetary gain, due to voltage profile improvement of a radial feeder is a very important aspect in the allocation of capacitors. This gain is even comparable to the savings due to peak-loss and energy-loss reductions. Best results are obtained when a combination of fixed and switched capacitors are used and located at different points along the feeder.